Pengaruh Karakteristik Pekerjaan Dan Karakteristik Individu Terhadap Kinerja Karyawan PT Bank BNI Wilayah 07 Makassar - Mansyur, Abdul; Dharmawati Djaharuddin; Sri Rahayu, Bela (Jurnal Ilmiah Bongaya, 2023)
This study aims to examine and analyze the effect of job characteristics and individual characteristics on employee performance at PT Bank Negara Indonesia Regional Office 07 Makassar. data collection using primary data, the type of research used is quantitative research. The population in this study were employees of PT Bank Negara Indonesia Regional Office 07 Makassar with 215 employees. The sample in this study amounted to 68 people based on the calculation of the slovin formula. The sampling technique used in this study is simple random sampling by taking samples from a population in a certain way so that members have the same opportunity to be selected. data collection method used is to distribute questionnaires, observation and documentation. The results of the questionnaire have been tested for validity and reliability, as well as tested for the classical assumptions of normality, assumptions of autocorrelation, multicollinearity, heteroscedasticity and assumptions of linearity. Methods of data analysis using descriptive statistical analysis techniques and inferential statistical analysis. Based on the t test and multiple linear regression analysis performed, it can be seen that the first hypothesis states that job characteristics have a positive and significant effect on employee performance, the second hypothesis states that individual characteristics have a positive and significant effect on employee performance, and the third hypothesis states that job characteristics and individual characteristics influence simultaneously on employee performance.